2022
DOI: 10.1002/adfm.202111271
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Synthetic Beta Cells for Insulin Biosynthesis and Release under Hyperglycemic Conditions

Abstract: Advances in artificial/synthetic cells have drawn a new era of nanobiotechnology, which have shown broad prospects in biomedical applications. The rational nanoengineering of synthetic cells that can closely substitute the systematic biological functions of cells is a next grand challenge. Here, a genetically encoded synthetic beta cell, which can sense hyperglycemic conditions to initiate programmed biosynthesis and secretion of insulin is reported. By encapsulating different metal–organic framework‐based art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Liu et al reported a MOF-based artificial β cell; the encapsulated MOF organelles sense hyperglycemia in the environment, start programmed insulin gene transcription and protein translation and then secrete insulin. 84 The structure of the natural cell membrane can be dynamically modified by enzyme remodeling of acyl chains and polar heads to regulate signal transduction or binding.…”
Section: Environmental Response Motility and Chemotaxismentioning
confidence: 99%
See 3 more Smart Citations
“…Liu et al reported a MOF-based artificial β cell; the encapsulated MOF organelles sense hyperglycemia in the environment, start programmed insulin gene transcription and protein translation and then secrete insulin. 84 The structure of the natural cell membrane can be dynamically modified by enzyme remodeling of acyl chains and polar heads to regulate signal transduction or binding.…”
Section: Environmental Response Motility and Chemotaxismentioning
confidence: 99%
“…24 Recently, Liu et al reported a genetically encoded artificial neural network β cell that senses hyperglycemia in the environment and synthesizes and secretes insulin to promote glucose uptake by mammalian cells. 84 Liu et al synthesized artificial cells with high blood compatibility and a long blood circulation time using erythrocyte membrane fragments containing hemoglobin and prefabricated polysaccharide polynucleotide aggregates containing GOx. 81 In the presence of glucose and hydroxyurea, this artificial cell continuously produces nitric oxide (NO), sends signals to vascular cells and induces vasodilation.…”
Section: Vessels For Encapsulation and Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this point, zeolite imidazole frameworks (ZIFs), including ZIF-8, ZIF-90, MAF-7, and so forth, are the favorable MOF matrices for enzyme immobilization due to their biocompatible synthesis conditions. A pioneering work by Liang, Falcaro, and co-workers has found that ZIF-8 could in situ crystallize around a given enzyme, analogous to the natural biomineralization . Utilizing this method, single or multiple enzymes are readily encapsulated into ZIFs, and the encapsulated enzymes display improved stability yet maintain desirable bioactivity. However, these ZIFs biohybrids are microcrystalline powders and hence are difficult to be mechanically processed and shaped in a controllable manner. This significantly limits the MOF biohybrid acting as the core element in large-scale industrial applications, such as portable biosensors.…”
mentioning
confidence: 99%